Prinzmetal Angina: A Case Report of Recurrent Ventricular Fibrillation - Gujejiani, Lali; Latsuzbaia, Kakhaber; Tsivilashvili, Jaba; Jalabadze, Khatuna; Kharebashvili, Maia; Jinjolia, Nato; Tetradze, Vakhtang; Taboridze, Iamze (European Scientific Journal, ESJ, 2026)
Prinzmetal angina, also known as vasospastic or variant angina, is characterized by episodic coronary artery spasm leading to transient myocardial ischemia, typically presenting with chest pain and transient ST-segment elevation on ECG. Although usually benign and reversible, severe cases may result in life-threatening ventricular arrhythmias, including ventricular fibrillation (VF). We report the case of a 66-year-old male with a history of hypertension and prior aortic root replacement who presented with recurrent VF secondary to coronary vasospasm despite optimal medical therapy. Electrocardiography demonstrated transient ST-segment elevation, and coronary angiography revealed moderate atherosclerotic stenosis with superimposed severe coronary vasospasm. Despite aggressive vasodilator therapy, the patient continued to experience recurrent malignant arrhythmias requiring multiple defibrillations. Ultimately, coronary stenting of the affected vessels led to clinical stabilization and cessation of arrhythmic events. This case highlights the diagnostic and therapeutic challenges of refractory vasospastic angina complicated by malignant ventricular arrhythmias and suggests a potential role for percutaneous coronary intervention in selected cases unresponsive to medical therapy.